MULTIMEDIA PEMBELAJARAN BERBASIS KOMPUTER SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA - Nursafitri, Laila (LP3M STAI DARUSSALAM LAMPUNG, 2013)
Multimedia learning is a component that can be used to support theinstructional process. It is based on the perception that learning will takeplace with a good, effective, and enjoyable if it is supported by a mediathat can attract the interest and attention of the students. Multimedia inteaching and learning can be used in three functions . First, multimediacan serve as an instructional tool. Second, it can serve as a multimediainteractive tutorial, for example in the simulation . Third, it can serve as asource of multimedia instructions to learn, for example, multimedia is usedto store a series of microscope slides or radiographs.Through multimedia learning, the subject matter could be more concretebecause the information submitted be made in the form of text, sound, andimages. The use of computer -based multimedia learning is expected tobecome more attractive, effective, and efficient in achieving the learningcompetencies, and be able to encourage students to be more active, generateinterest and motivation to study so it will have a positive impact on studentlearning outcomes.Keywords: Multimedia learning, Learning outcomes.